Leukocyte recruitment in flavivirus-induced encephalitis - Slowikowski, Emily; Willems, Céleste; Marques, Pedro Elias (Frontiers in Immunology, 2025)
Flaviviruses are capable of causing a myriad of diseases in humans, including viral encephalitis. This condition involves complex interactions between the virus, resident cells of the central nervous system and leukocytes recruited to the brain. We reviewed the mechanisms underlying leukocyte recruitment during flavivirus-induced encephalitis with a focus on the role of various chemoattractants and adhesion molecules. We discuss how these molecules orchestrate the migration of peripheral leukocytes into the brain parenchyma and how neurotropic flaviviruses induce this process. Moreover, we discuss evidence of leukocytes both controlling viral propagation and contributing to neuropathology, which poses a challenge for therapy development. This review summarizes our current understanding of the mechanisms behind leukocyte recruitment during encephalitis, addresses the gaps that remain in the field, and presents opportunities for therapeutic targeting unveiled by recent research on flaviviral encephalitis.